A retrospective study of surgical and conservative treatment for spinal extradural abscess - Grieve, J. P. (Springer-Verlag, 2000)
The management of spinal extradural abscess (SEA), particularly the choice between surgical and conservative treatment, is controversial. We therefore undertook a retrospective study of patients admitted with this diagnosis: Details of presentation, treatment and outcome were obtained by review of inpatient notes and radiology. Twenty-five ¶individuals with SEA aged 10–¶79 years were admitted between 1989 and 1995. Nine were treated non-operatively with antibiotics, of which three also underwent diagnostic CT-guided biopsy, and 16 underwent surgical drainage. There was no significant difference in the neurological features at presentation between the two groups. Two patients (8%) died; 11 (44%) patients remained the same and 12 (48%) improved following treatment. Four patients treated conservatively (44%) and seven treated surgically (43%) were capable of return to work or school, whilst a further seven patients (three treated conservatively and four treated surgically) were able to lead independent lives. No significant difference in outcome was demonstrated between patients treated non-operatively and those treated surgically. We conclude that certain carefully selected patients can be treated conservatively, but that surgery should remain the mainstay of management.